Fast carbidization of silicon in additive manufactured Si-C-SiC composite - Tsovinar Ghaltaghchyan; Khachik Nazaretyan; Viktorya Rstakyan; Marina Aghayan (Results in Materials)
Silicon carbide-based composites are advantageous material for electronic industry. Their application is limited by the difficulty to fabricate complex structural parts. This research used powder bed additive manufacturing technology, particularly selective laser melting, to manufacture silicon carbide-based composite. However, during the laser sintering silicon carbide decomposed to silicon and carbon. Further carbidization of free silicon faces the challenge of silicon carbide (SiC) formation, which can prevent further reaction between the reacting elements.To enhance the carbidization process we heated the samples with ultra-high heating rates (2000 °C/min) employing High-Speed Temperature Scanning (HSTS) technique using direct electrical current to heat the sample. Formation of silicon carbide takes place, achieving higher density of the samples. We have compared the results with the samples heated at relatively lower heating rates (100 °C/min). The mechanism of interaction was explained.The heating rate has critical effect on silicon carbide formation, impacting the atomic diffusion rate between silicon and carbon, final microstructure and density of the samples. The silicon carbidization process can be achieved by direct heating the samples at ultra-high heating rates.